The Mitochondria-Targeted H2S-Donor AP39 in a Murine Model of Combined Hemorrhagic Shock and Blunt Chest Trauma. Issue 2 (August 2019) - Wepler, Martin; Merz, Tamara; Wachter, Ulrich; Vogt, Josef; Calzia, Enrico; Scheuerle, Angelika; Möller, Peter; Gröger, Michael; Kress, Sandra; Fink, Marina; Lukaschewski, Britta; Rumm, Grégoire; et al.
Abstract : ABSTRACT: Hemorrhagic shock (HS) accounts for 30% to 40% of trauma-induced mortality, which is due to multi-organ-failure subsequent to systemic hyper-inflammation, triggered by hypoxemia and tissue ischemia. The slow-releasing, mitochondria-targeted H2 S donor AP39 exerted beneficial effects in several models of ischemia-reperfusion injury and acute inflammation. Therefore, we tested the effects of AP39-treatment in a murine model of combined blunt chest trauma (TxT) and HS with subsequent resuscitation. Methods: After blast wave-induced TxT or sham procedure, anesthetized and instrumented mice underwent 1 h of hemorrhage followed by 4 h of resuscitation comprising an i.v. bolus injection of 100 or 10 nmol kg −1 AP39 or vehicle, retransfusion of shed blood, fluid resuscitation, and norepinephrine. Lung mechanics and gas exchange were assessed together with hemodynamics, metabolism, and acid-base status. Blood and tissue samples were analyzed for cytokine and chemokine levels, western blot, immunohistochemistry, mitochondrial oxygen consumption (JO2 ), and histological changes. Results: High dose AP39 attenuated systemic inflammation and reduced the expression of inducible nitric oxide synthase (iNOS) and IκBα expression in lung tissue. In the combined trauma group (TxT + HS), animals treated with high dose AP39 presented with the lowest mean arterial pressure and thus highest norepinephrine requirements and higher mortality. Low dose AP39 had no effects on hemodynamics, leading to unchanged norepinephrine requirements and mortality rates. Conclusion: AP39 is a systemic anti-inflammatory agent. In our model of trauma with HS, there may be a narrow dosing and timing window due to its potent vasodilatory properties, which might result in or contribute to aggravation of circulatory shock-related hypotension. Abstract : Supplemental Digital Content is available in the text